Publication trend of COVID-19 and non-COVID-19 articles in the Indian Journal of Ophthalmology during the pandemic - Bharat Gurnani; Kirandeep Kaur (Indian Journal of Ophthalmology, 2021)
Purpose: To analyze the trend of COVID-19-related and non-COVID-19-related articles published in the Indian Journal of Ophthalmology (IJO) during the COVID-19 pandemic. Methods: A retrospective analysis of all COVID-19 and non-COVID-19-related articles published in all the issues of IJO from January 2020 to March 2021 was performed. The data were obtained from the official website of IJO, Editor IJO monthly email, and PubMed. The monthly data were analyzed and a comparative analysis was done. The articles were segregated as Original, Review, Case Report/Series, Letter to the Editor/Commentary, Guest Editorial, Research methodology, Point-Counterpoint, Consensus Criteria, Ophthalmic Images, Photo Essay, Surgical Techniques, and AIOS Meeting Papers. Results: Out of 1343 articles published in IJO during the pandemic, 182 (13.55%) were COVID-19-related and 1161 (86.45%) were non-COVID-19-related articles. Among COVID-19 articles (182), majority were letter to the editors 66 (36.26%), followed by original articles 39 (21.42%), commentaries 24 (13.18%), editorials 18 (9.89%), and preferred practices 13 (7.14%). The least were case reports five (2.74%), current ophthalmology and innovation three (1.64%) each, and one (0.54%) each of consensus criteria, images, and photo assays. In the non-COVID-19-related articles (1161), maximum were original articles 276 (23.77%), followed by case reports 179 (15.41%), photo assays 157 (13.52%), and commentaries 141 (12.14%). The least were three (0.25%) consensus criteria and two (0.17%) each of current ophthalmology and innovations. The lockdown issue with 223 articles, postlockdown phase 1 had 267, postlockdown phase 2 had 321, and postlockdown phase 3 with 316 (1127 articles) articles in IJO showed a rising trend in a number of published articles compared with the prelockdown issues (216 articles). Conclusion: The quality and quantity of articles published in IJO increased and improved significantly. The results were seen with progressive improvement in citations and impact factors of the journal.